Gender empowerment and female-to-male smoking prevalence ratios - Sara C Hitchman; Geoffrey T Fong (The World Health Organization, 2011)
OBJECTIVE: To determine whether in countries with high gender empowerment the female-to-male smoking prevalence ratio is also higher. METHODS: Bivariate and multiple regression analyses were performed to explore the relation between the United Nations Development Programme's gender empowerment measure (GEM) and the female-to-male smoking prevalence ratio (calculated from the 2008 WHO global tobacco control report ). Because a country's progression through the various stages of the tobacco epidemic and its gender smoking ratio (GSR) are thought to be influenced by its level of development, we explored this correlation as well, with economic development defined in terms of gross national income (GNI) per capita and income inequality (Gini coefficient). FINDINGS: The GSR was significantly and positively correlated with the GEM (r = 0.680; P < 0.001). In addition, the GEM was the strongest predictor of the GSR (β, adjusted: 0.47; P < 0.0001) after controlling for GNI per capita and for Gini coefficient. CONCLUSION: Whether progress towards gender empowerment can take place without a corresponding increase in smoking among women remains to be seen. Strong tobacco control measures are needed in countries where women are being increasingly empowered.